Comparison Study of Method for Calculation of Mesh Efficiency of Involute Gear Pair - Chen Yinglin Chen Jiangyi (Jixie chuandong)
The efficiency of kinematic pairs is often formulated with work or force as it is done for the calculation of mesh efficiency of involute gear pair. Taking the distance between pitch point and contact point as a variable, two expressions of instantaneous efficiency of gear pair are derived from the perspective of work and force. Averaging the instantaneous efficiency along contact line leads to mesh efficiency of gear pair. Numerical examples are used to assess the validity of the presented calculation methods and the influences of the transmission ratio, pinion teeth number and friction coefficient on mesh efficiency are analyzed. Comparison of numerical results shows the calculation method based on the force is more appropriate than the method based on the work.